Pengaruh Non Performing Loan (NPL), Return On Asset (ROA), dan Capital Adequacy Ratio (CAR) Terhadap PBV Pada Bank BUMN Yang Terdaftar di Bursa Efek Indonesia - Masita Wahyuni Asih; Fausiah Fausiah; Andi Herman Tellu (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Masita Wahyuni Asih 2024, The Effect of Non Performing Loan (NPL), Return on Asset (ROA), and Capital Adequacy Ratio (CAR) on Price to book value (PBV) at BUMN Banks listed on the Indonesia Stock Exchange for the 2018-2023 Period. Makassar STIM-LPI Management Science Study Program (supervised by Fausiah, S.E., M.Si. and Andi Herman Tellu, S.E., M.M.). The purpose of this study was to determine the effect of Non Performing Loan (NPL), Return on Asset (ROA), and Capital Adequacy Ratio (CAR) on Price to Book Value (PBV) at BUMN banks listed on the Indonesia Stock Exchange both partially and simultaneously. Price to Book Value (PBV) is the dependent variable (Y), and three independent variables (X) are used, namely Non Performing Loan (NPL), Return on Asset (ROA), and Capital Adequacy Ratio (CAR). Saturated sampling was used to obtain secondary data from a population of 4 banking companies listed on the Indonesia Stock Exchange. Descriptive statistics and classical assumptions, such as multicollinearity assumption and heteroscedasticity assumption, have been tested in relation to the research findings. The data analysis approach uses panel data regression, hypothesis testing, and the Fixed Effect Model (FEM) test. The partially tested study results show that while non-performing loans (NPLs) do not affect price to book value (PBV) significantly, there are return on assets (ROA) and capital adequacy ratio (CAR) that do. The findings of this study also simultaneously show that PBV is significantly affected by NPL, ROA, and CAR.